Correlation Between Educational Performance, Family Background and Settlement Type in Covasna County, Romania - Barabás, Andrea; Bacskai, Katinka (Central European Journal of Educational Research, 2020)
In social sciences, a more sophisticated way of examining students' school performance, based on the combination of school and family factors, is becoming increasingly popular. Important indicators of schools operating in a given territorial and societal context can be obtained both at student and institutional levels if territorial characteristics are included. In our research we examine the correlation between family background and performance, and investigate the settlement type where the proportion of students from low SES schools is the highest. At the same time we are also curious whether there is a greater chance of resilience in smaller communities. Our results show that the majority of students from low SES schools study in small settlements, but resilience is clearly not more typical in smaller communities.